Penerapan Isyarat Huruf Hijaiyyah dalam meningkatkan kemampuan membaca Al-Qur’an bagi anak tunarungu - Nurdyansyah, Nurdyansyah; Pujiati, Nunuk (Literal: Disability Studies Journal, 2023)
This study intends to describe the implementation of learning techniques "Hijaiyyah letter signs" to improve the reading ability of the Qur'an for children with hearing loss. Hijaiyyah letter signs are very helpful for deaf children who have hearing impairments in improving their ability to read the Qur'an. A descriptive qualitative research approach was used in this study. In this study, observation, interviews, and documentation were used as data collection methods. To ensure the correctness and validity of the data, the analytical method in this study uses data triangulation, namely checking the consistency between the results of interview data, observation data, and documentation data. Before applying Hijaiyyah letter cues, the ability of deaf children to read the Qur'an showed an average value of 52.45, after applying Hijaiyyah letter cues, the ability to read Al-Qur'an showed an average value of 79.85. This leads to the conclusion that the use of Hijaiyyah sign language has a significant positive impact on the ability of deaf children to read the Qur'an.